Strategi Guru PAI Dalam Mengembangkan Pembelajaran Pendidikan Agama Islam di SMAN 3 Kota Padang - Yusrianto, Yusrianto (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to evaluate the effectiveness of Islamic Religious Education (PAI) learning strategies at SMA 3 Padang. A qualitative descriptive method was employed, utilizing interviews, observations, and documentation for data collection. The findings revealed that inquiry-based strategies, direct practice, and interactive approaches significantly enhance students’ understanding of religious values. Flagship programs such as Quran memorization (tahfizul Quran), funeral prayer practices, and Islamic extracurricular activities greatly contribute to shaping students' religious character. The results are analyzed using constructivism theory, social learning theory, and value education theory, emphasizing the importance of experiential learning and value internalization. This study recommends optimizing strategies and programs to support more effective PAI learning.